Lattices of topologies of algebraic systems - Arnautov, V.I.; Filippov, K.M. (Algebra and Discrete Mathematics, 2006)
The article is based on the report, which was delivered on a plenary sitting on the 5th International Algebraic Conference in the Ukraine (Odessa, July, 2005) and is a survey of the results on the lattices of topologies of different algebraic systems.